The photosensitizing activity of lumazine using 2'-deoxyguanosine 5'-monophosphate and HeLa cells as targets - Denofrio, María Paula (2009)
Lumazines are an important family of heterocyclic compounds present in biological systems as biosynthetic precursors and/or products of metabolic degradation. Upon UV irradiation, the specific compound called lumazine (pteridine-2,4(1,3H)-dione) is able to generate singlet oxygen (1O2), which is one of the main chemical species responsible for photodynamic effects. To further assess the photosensitizing capability of lumazine (Lum) experiments were performed using the nucleotide 2′-deoxyguanosine 5′-monophosphate (dGMP) and, independently, cervical cancer cells (HeLa cell line) as targets. In the dGMP experiments, the data revealed that dGMP indeed undergoes oxidation/oxygenation photoinduced by Lum. Moreover, dGMP disappearance proceeds through two competing pathways: (1) electron transfer between dGMP and excited-state Lum (Type I process) and (2) reaction of dGMP with 1O2 produced by Lum (Type II process). The multistep processes involved are convoluted and susceptible to changes in experimental conditions. The independent studies with HeLa cells included fluorescence analysis of cell extracts and phototoxicity experiments performed at the single-cell level. Results showed that, upon Lum uptake and irradiation, photodynamic effects occur. In particular, the mitochondria and cell membrane were perturbed, both of which reflect key stages in cell death. The data reported herein illustrate how the irradiation of an endogenous biological compound can have various effects which, depending on the system, can be manifested in different ways.